The Traces of Qur’anic Women’s Hakiki Justice Interpretation in KUPI's Fatwas - Rofiah, Nur; Nikmatullah, Nikmatullah; Mufidah, Zakiyatul (UIN Sunan Kudus, 2024)
Mainstream Islamic epistemologies are gender biased due to two primary reasons. First, women are often seen as men’s sexual tools and reproductive machinery, making them sexual objects. Second, legalistic interpretations of the Qur’an require formal interpretation. The Indonesian Women Ulama Congress (KUPI) proposes an alternative Qur'anic women's Hakiki Justice interpretation. In this context, women are respected as whole persons with physical, intellectual, and spiritual qualities deserving of respect as complete subjects. Islamic welfare ideals are shaped by their unique bodily and social human experiences. Islamic teaching system consists of vision, moral foundation, and method verses. As a process of transformation, the verses comprise the starting point, intermediate, and final goals verses. KUPI’s fatwas are examined for Qur'anic women's hakiki justice interpretation. The library research method is employed using credible books and online resources. The key texts are Nalar Kritis Muslimah, Metodologi Fatwa KUPI books, and KUPI's fatwas documents on the Kupipedia website. The results highlight that the traces of Qur'anic women's hakiki justice interpretation in KUPI's fatwas are indicated by how KUPI integrated women's bodily and social experiences in understanding the issues and the Qur'an.